Electrophysiological evidence of sustained spatial attention effects over anterior cortex: Possible contribution of the anterior insula. (30th March 2019) - Berchicci, Marika; Ten Brink, Antonia Francisca; Quinzi, Federico; Perri, Rinaldo Livio; Spinelli, Donatella; Di Russo, Francesco
Abstract: Spatial attention can improve performance in terms of speed and accuracy; this advantage may be mediated by brain processes at both poststimulus (reactive) and prestimulus (proactive) stages. Here, we studied how visuospatial attention affects both proactive and reactive brain functions using event‐related potentials (ERPs). At reactive stage, effects of attention on parietal‐occipital components are well documented; little data are available on anterior components. Seventeen participants performed simple and discriminative response tasks, while voluntarily and steadily attending either the left or right visual hemifield throughout one block. Response speed was faster for the attended side. At ERP level, attending to one hemifield did not produce lateralization of proactive components—that is, the BP and the pN. As for poststimulus components, we confirmed the well‐known amplitude effects on the P1, N1, and P3. More interesting are results for the prefrontal components previously neglected in tasks modulating spatial attention. Previous studies suggest that these components reflect perceptual and sensory‐motor awareness (pN1 and pP1 components), and stimulus‐response mapping (pP2 component) associated to anterior insular activity. Spatial attention enhanced the pN1 and the pP1 amplitude but had no effect on the pP2. Overall, results extend knowledge on spatial attention, showing that sustained spatial attention affects the activity of anterior areas, such as the anterior insula, in addition to the known influence on occipital‐parietal areas. Top‐down spatial attention is likely mediated by increased sensory and sensory‐motor awareness for attended events; this effect is evident in reactive, not proactive, brain activity. Abstract : Spatial attention can improve performance, and this advantage may be mediated by brain processing at both pre‐ and poststimulus stages. By means of event‐related‐potentials (ERPs) and behavioral measures, here we show that orienting attention toward one side produces faster responses, and this advantage seems to be mainly mediated by processing at poststimulus (reactive) stage. Indeed, sustained spatial attention not only affects the activity on occipital‐parietal areas but also modulates the more anterior areas, such as the anterior insula. Top‐down spatial attention is likely mediated by increased sensory and sensory‐motor awareness for attended events.